Traumatic upper limb injuries during the men's field hockey junior World Cup 2009 - Mukherjee, S. (Research in Sports Medicine, 2013)
This study was a prospective epidemiological investigation of upper limb injuries during the Men's Field Hockey Junior World Cup 2009. Three hundred twenty-four players were observed in 58 matches of the tournament. Twenty-eight upper limb-related injuries were documented. The injury incidence was 0.48 per match and 19 per 1,000 match hours. Most injuries were due to contact with the ball, and the left hand was the most commonly injured part. Contusion was the most common type of injury. The odds ratio for hand and wrist injuries in players not wearing gloves was 4.01 (95% CI, 0.52-30.62), and the relative risk of hand and wrist injuries in players wearing gloves was 0.26 (95% CI, 0.03-1.92). Male youth hockey players are at a high risk of upper limb, especially hand and wrist, injuries during major international tournaments and that use of protective gloves can provide significant protection against hand and wrist injuries in the sport.